CFD and experimental evaluation of R744 transcritical gas cooler used in solar assisted heat pump system - Baradey, Yehya (Elixir, 2020)
In this paper, a helical coil tube in tube heat exchanger was designed and used in carbon dioxide solar assisted heat pump system (SAHP) to provide hot water for domestic applications and to operate an air gap membrane desalination (AGMD) unit. Both theoretical and experimental studies to investigate the performance of the gas cooler with Glycol Ethylene 50% and water as coolants were performed. The experimental part to study the behavior of the carbon dioxide in the supercritical region was conducted on the R744 heat pump test rig located at Department of Energy and Process Engineering –NTNU. On the other hand, FEA using ANSYS Fluent 18.1 was used to conduct the theoretical analysis. The study includes effect of inlet temperature of both coolants, effect of discharge pressure, effect of mass flow rate of water, and logarithmic mean temperature difference (LMTD). Good agreements between Experimental and simulation results were achieved. Results showed that the outlet temperature of the refrigerant from the gas cooler decreased from 81 °C to 40 °C, with 0.085 bar average pressure drop due to the heat rejection process. The outlet temperature of the refrigerant from the gas cooler in case of water is 8 °C lower than with ethylene glycol 50%. The outlet temperature of water reached 57 °C which is enough for domestic applications and to operate the AGMD unit to produce fresh water. It is observed that the pressure drop in the refrigerant by using water as coolant is higher by 0.2 bar than when ethylene glycol 50% used. Results also revealed that the value of LMTD of the gas cooler using ethylene glycol 50% is 24.3 % higher than the LMTD value when using water.